2019
DOI: 10.1101/756486
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An evaluation of Nephrology Literature for Transparency and Reproducibility Indicators: Cross-sectional Review

Abstract: Background:Reproducibility is critical to diagnostic accuracy and treatment implementation. Concurrent with clinical reproducibility, research reproducibility establishes whether the use of identical study materials and methodologies in replication efforts permit researchers to arrive at similar results and conclusions. In this study, we address this gap by evaluating nephrology literature for common indicators of transparent and reproducible research. Methods:We searched the National Library of Medicine catal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Specifically, we noted that only one of the 59 articles that declared data was available complied with our FAIR assessment. This observation, depending on how availability for reuse is defined, is unfortunately consistent with this body of research which has reported 50-100% reductions in availability following interrogation of sharing statements 15-25 ; with factors such as the lack of unique and permanent identifiers, meta-data and licensing terms being noted as major pitfalls. 30,47 Furthermore, while we also noted a strong relationship between mandatory data sharing policies and actual data availability, we unfortunately also observed similarly sub-optimal compliance with these policies too; a finding that has been noted by other studies both inside and outside of medicine.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Specifically, we noted that only one of the 59 articles that declared data was available complied with our FAIR assessment. This observation, depending on how availability for reuse is defined, is unfortunately consistent with this body of research which has reported 50-100% reductions in availability following interrogation of sharing statements 15-25 ; with factors such as the lack of unique and permanent identifiers, meta-data and licensing terms being noted as major pitfalls. 30,47 Furthermore, while we also noted a strong relationship between mandatory data sharing policies and actual data availability, we unfortunately also observed similarly sub-optimal compliance with these policies too; a finding that has been noted by other studies both inside and outside of medicine.…”
Section: Discussionsupporting
confidence: 79%
“…Rather our observations that 19% and 4% of cancer researchers declared data and code were publicly available respectively are consistent with several studies reporting low, but increasing, declaration rates ranging between 3-24% and 0-2% respectively over several medical disciplines between 2014-2018. [15][16][17][18][19][20][21][22][23][24][25] The increase of declarations over time -particularly data availability declarations -is likely due to the growing number of medical journals that are adopting stronger policies on data and code sharing, particularly those that are requiring the addition of availability statements. For example, we note that a quarter of the unique 235 journals analysed in our study had adopted a mandatory data sharing policy for some or all data, which is higher than a previous survey of medical journal editors in the previous year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproducibility of systematic reviews, however, is very difficult if not impossible to undertake. The senior author of this study widely evaluates research reproducibility [41][42][43][44][45][46][47][48][49] and has evaluated the reproducibility of meta-analyses. 50 While meta-analytic effect estimates may be more reproducible in some cases, earlier steps of the systematic review process are likely not.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…S3 Fladie et al have evaluated the nephrology literature for indicators of transparency and reliability of research. 9 The authors have gone to lengths to make the process for this article transparent and reproducible. They randomly sampled 172 articles from English language nephrology over 5 years (2014À2018).…”
mentioning
confidence: 99%